Perceptions and experiences of fertility preservation in female patients with cancer in Greece - Anna-Maria Taniskidou; Polychronis Voultsos; Vasileios Tarlatzis; Eleni Timotheadou (BMC, 2024)
Abstract Background As advances in oncology have led to remarkable and steady improvements in the survival rates of patients with cancer and anticancer treatment can cause premature ovarian failure in women, fertility preservation (FP) has become a global public health concern and an integral part of the care for women diagnosed with cancer during reproductive age. However, for various reasons, FP remains underutilized for patients with cancer. There are substantial gaps in our knowledge about women's experiences and perceptions of the issue. This study aims to contribute to bridging that gap. Methods This prospective qualitative study was conducted from March 2018 to February 2023. A combination of purposive and snowball sampling was used. Data were collected by semistructured interviews with nineteen reproductive-age women who had been recently diagnosed with cancer. Data were classified and analysed with a thematic analysis approach. Results A variety of distinct themes and subthemes emerged from the analysis of the interview data. The cancer diagnosis emerged as a factor that considerably affects the women's attitudes towards biological parenthood: It can further increase their (strong) previous desire or decrease their previous (weak) desire. Women with a recent cancer diagnosis had not received adequate and multidisciplinary counselling, including clear and sufficient information. However, participants felt satisfied with the information they received because they either received the information they requested or remained in denial about the need to be informed (i.e., because they felt overwhelmed after the cancer diagnosis). Embryo cryopreservation emerged as a less desirable FP option for women with cancer. Participants showed respect for human embryos, not always for religious reasons. Surrogacy emerged as the last resort for most participants. Religious, social or financial factors did play a secondary (if any) role in women's decision-making about FP. Finally, male partners' opinions played a secondary role in most participants' decision-making about FP. If embryo cryopreservation was the selected option, partners would have a say because they were contributing their genetic material. Conclusions The findings that emerged from the data analysis were partly consistent with prior studies. However, we identified some interesting nuances that are of clinical importance. The results of this study may serve as a starting point for future research.